2017
DOI: 10.3892/mmr.2017.8303
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MEG3 ameliorates respiratory syncytial virus infection by suppressing TLR4 signaling

Abstract: Maternally expressed gene 3 (MEG3), a long noncoding RNA (lncRNA) has been dysregulated in various tumors. However, the expression level and functional role of MEG3 in the progression of respiratory syncytial virus (RSV) infection remains to be elucidated. The present study quantified the expression level of MEG3 in the nasopharyngeal (NPA) samples of RSV‑infected patients and in BEAS‑2B cells infected with RSV. The findings of the present study demonstrated that the expression level of lncRNA MEG3 was reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Our data from both immortalised cell lines and WD-PBECs indicated that TLR4 is implicated in RSV infection and/or replication. This is consistent with a recent report demonstrating a protective role of MEG3, a long noncoding RNA, against RSV infection, which most likely acts through the inhibition of the TLR4 signalling pathway(22).…”
Section: Discussionsupporting
confidence: 93%
“…Our data from both immortalised cell lines and WD-PBECs indicated that TLR4 is implicated in RSV infection and/or replication. This is consistent with a recent report demonstrating a protective role of MEG3, a long noncoding RNA, against RSV infection, which most likely acts through the inhibition of the TLR4 signalling pathway(22).…”
Section: Discussionsupporting
confidence: 93%
“…Total proteins were extracted using a total protein extraction kit (Beijing Solarbio Science and Technology Co., Ltd.), and protein concentration was determined by the BCA protein assay kit (Pierce; Thermo Fisher Scientific, Inc.). Western blotting was performed as previously described [32]. The antibodies used were as follows: phosphatidylinositol-4,…”
Section: Western Blottingmentioning
confidence: 99%
“…As much as 80% of the host genome is transcribed to nontranslated RNA, which underscore the potential importance of host non-coding RNA (ncRNA) in the host-virus interaction. Accumulating evidence shows that host ncRNAs play key regulatory roles during viral replication and infection (Lamontagne et al, 2015;Ding et al, 2016;Landeras-Bueno and Ortin, 2016;Liu and Ding, 2017;Trobaugh and Klimstra, 2017;Tao et al, 2018). To date, few studies have been published about the functions of ncRNAs in HTNV infection.…”
Section: Introductionmentioning
confidence: 99%